Elraglusib (formerly 9-ING-41) possesses potent anti-lymphoma properties which cannot be attributed to GSK3 inhibition - Josh T. Coats; Sudhir Tauro; Calum Sutherland (Cell Communication and Signaling, 2023)
Abstract Elraglusib (formerly 9-ING-41) is an ATP-competitive inhibitor of glycogen synthase kinase-3β (GSK3β) undergoing clinical trials for the treatment of various cancers including non-Hodgkin lymphoma (NHL). The drug reduces proliferation of several NHL cell lines and has efficacy in xenograft models of the disease. To confirm the importance of its action on GSK3β, we treated 3 lymphoma cell lines with selective, structurally distinct GSK3 inhibitors: CT99021, SB216763, LY2090314, tideglusib, and elraglusib. Stabilization of β-catenin and reduced phosphorylation of CRMP2, two validated targets of GSK3, were used as functional read-outs for GSK3 inhibition. CT99021, SB216763, and LY2090314 failed to reduce proliferation or viability in any cell line at concentrations that stabilized β-catenin and reduced CRMP2 phosphorylation. There was partial reduction of CRMP2 phosphorylation but no significant effect on β-catenin at cytotoxic doses of elraglusib. There was no indication of GSK3 inhibition at doses of tideglusib that affected cell viability and apoptosis. Cell-free kinase screening confirmed several other targets of elraglusib, distinct from the GSK3 inhibitors with no anti-lymphoma actions, including PIM kinases and MST2. These data question GSK3 as the target of elraglusib in lymphoma, and hence the utility of GSK3 expression as a ‘stand-alone’, therapeutic biomarker in NHL. Video Abstract